Fresh air in the 21st century? - Prather, Michael; Gauss, M; Berntsen, T; Isaksen, I; Sundet, J; Bey, I; Brasseur, G; Dentener, F; Derwent, R; Stevenson, D; Grenfell, L; Hauglustaine, D; et al. (Geophysical Research Letters, 2003)
Two sets of sea surface temperature/sea ice changes are used to test the sensitivity of tracer transport to the pattern of warming in the doubled CO2 climate. One set (2CO2WT) has greater tropical and high latitude sea surface temperature changes than the other (2CO2), although both fall within the range of plausible response. Simulations were done both with and without interactive ozone. Results show that the SST pattern affects the circulation change throughout the troposphere and middle atmosphere; the ozone interaction affects primarily the upper stratosphere, but through wave-mean flow interaction has effects that extend down into the upper troposphere. Both experiments feature increased tropospheric/stratospheric exchange at low latitudes and greater vertical mixing within the troposphere; only the WT experiments result in increased interhemispheric transport and a more direct circulation in the high latitude stratosphere. Ozone increases in the upper stratosphere and decreases in the lower stratosphere in all the simulations, with greater transport of high latitude ozone into the troposphere in the WT runs. At sea level there is a more positive phase of the Arctic Oscillation (AO)-type oscillation, and this is also true at 100 mbar, but there is no significance in the middle troposphere and the sign is different in the middle stratosphere. Many of these results differ from those generated in older versions of the GISS GCMAM despite the same SST forcing due to differences in control run characteristics, which has implications for model intercomparison experiments.